PENGUATAN NILAI KETAUHIDAN DALAM PRAKSIS PENDIDIKAN ISLAM - Benny Prasetiya; Sofyan Rofi; Bahar Agus Setiawan (JIE (Journal of Islamic Education), 2018)
Tawhid value is the most essential thing in internalizing the values of Islamic education in aspects of life. Tawhid is a fundamental thing to determine determination and confidence in the implementation of the values of Islamic teachings. The value of monotheism is not only used as "subject matter" but rather as a system pengutan and concepts that underlie the entire Islamic education system. In other words tauhid will be the basis for the overall activity of the Islamic education process.